Phase II study on hepatic arterial infusion chemotherapy using percutaneous catheter placement techniques for liver metastases from colorectal cancer (JFMC28 study). Issue 1 (12th January 2015) - Arai, Yasuaki; Aoyama, Toru; Inaba, Yoshitaka; Okabe, Haruumi; Ihaya, Takashi; Kichikawa, Kimihiko; Ohashi, Yasuo; Sakamoto, Junichi; Oba, Koji; Saji, Shigetoyo
Abstract Aim This prospective multicenter study aimed to evaluate the efficacy and adverse events of hepatic arterial infusion chemotherapy (HAIC) using percutaneous catheter placement techniques for liver metastases from colorectal cancer (CRC). Methods We administered 5‐fluorouracil at 1000 mg/m2 over 5 h via hepatic arterial infusion on a weekly schedule. The primary endpoint was the overall response rate (RR). The secondary endpoints were the overall survival (OS), progression‐free survival (PFS) and toxicities. Results Between February 2000 and March 2002, seventy‐seven eligible patients were enrolled in this study. After a median of 26 treatment cycles, 4 patients achieved a complete response, 29 achieved a partial response, 28 had stable disease, 15 had progressive disease and the status of one patient was unknown. The overall RR was 42.9% and the disease control rate (DCR) was 79.2%. The median PFS and OS times were 203 and 560 days, respectively. The most common grade 3 or 4 hematological and non‐hematological toxicities were total bilirubin level elevation (10.4%) and gamma‐glutamyl transferase level elevation (10.4%). With regard to the relationship between the background factors and treatment outcomes, the DCR, RR, PFS and OS were different between patients with and without extrahepatic lesions (DCR: 86.5% vs 64%, RR: 46.2% vs 36.0%, PFS: 233 days vs 99 days, OS: 587 days vs 558 days). Conclusion The primary endpoint of this study was not met. HAIC using percutaneous catheter placement techniques did not improve the RR for liver metastasis from CRC.